Mapeamento de vazios urbanos em uberlândia utilizando o geoprocessamento: o caso do bairro santa mônica - Silva, Tarcísio Marques da (2006)
This work has as objective indentify and to map the evolution of the occupation of empty areas and verifying if there was urban land speculation. To this work were used aereophotography and geoprocessament. The Study Area had choosen was part of Santa Mônica District, at Uberlândia-MG. The map of the empty areas was made from AutoCAD 2007 and Arcview 3.2, using cadastral plan of 1983, aereo photography of the 1997 and 2004. The results an area that had in 1982, 1997 and 2004 respectively 37, 20, 11 per cent of the empty areas. The big number of the empty areas in 1982 can be explained in function of the Avenues that was a railway, linking Goiás to São Paulo and crossing the city. Years after there were an strong ocupation in the more dense areas and a valorization in the areas in front of the railways (actual João Naves de Ávila Avenue) thanks Directors Plans, Urban Zones, public investiment and the construction of the equipaments that atract strong vehicles flows and peoples, as a Univesity, a Shopping Center and the local public administration.